Physical Characteristics of Edible Film Gel Made under Various pH and Ratio of Casein and Tapioca - Triana Lindriati; Yhulia Praptiningsih; Dwi Fatma Wijayanti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2014)
Gelation from casein and tapioca take place in the edible film making. An interaction of carbohydrate and protein in the formation of gel could be affect on the physical properties of edible film gel. An appropriate ratio of casein-tapioca and pH was expected to produce physical characteristics of edible film gel. The aims of this research were to know the influence of casein- tapioca ratio, pH and the interaction of casein-tapioca ratio and pH to produce edible film gel. The research was conducted by randomized completely block design with two factors. The first factor was casein-tapioca ratio (0:100; 20:80; 40:60; 60:40; 80:20; 100:0) and the second factor was pH (4; 7; 9). The parameter of observation were colour (lightness and chroma), moisture content, WHC, precipitation and viscosity of edible film gel. The data analysis uses minitab V.1.6 carried on Tukey test. The result shows that casein-tapioca ratio influenced on colour (lightness and chroma), moisture content, WHC, precipitation and viscosity of edible film gel. The treatment of pH influenced on colour (lightness and chroma), moisture content, WHC and precipitation of edible film gel. An interaction between the ratio of casein-tapioca and pH influenced on colour (lightness and chroma), moisture content, WHC and precipitation of edible film gel. Keywords: Edible film gel, interaction of carbohydrate-protein, physical characteristics